A hospital-based cross-sectional study on yoga and meditation in patients of hypertension in Western India - Sarkar, Amrita; Roy, Debjit; V. Bundela, Chintan; Gohel, Aniruddha; R. Makwana, Naresh; V. Parmar, Dipesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Yoga and meditation hold promise as a non-pharmacological management of hypertension as they have shown to lower blood pressure. This study aimed at (1) assessing the awareness about benefits of yoga and meditation in hypertension among patients and finding its socio-demographic correlates, (2) estimating the practice of yoga and meditation in hypertensives, its pattern and impact on blood pressure control. Methods: This cross-sectional study was conducted on 400 hypertensive patients. Statistical association was tested with chi square and independent t tests. Results: It was observed that only 9% respondents were aware of the benefits of yoga and meditation in hypertension while 12.8% practised the same. On probing it was found that these 3.8% practised yoga and meditation only because their physician had advised them to do so without even knowing their benefits. This points out the importance of physician advice which can be even more effective if pros and cons are properly explained. People who were aware of the benefits were 51.9 times more likely to practise them (p<0.001). Highly significant association was observed between awareness regarding lifestyle modifications like yoga and meditation and gender, socioeconomic status, education and locality (urban non-slum/urban slum/rural). Conclusions: The complementary use of non-pharmacological treatment or lifestyle modifications like yoga and meditation can go a long way to lower blood pressure and such options need to be provided by the health care providers and the gap in awareness elicited in our study needs to be addressed.